Pediatric Specialty Nursing Associations and their Role in Leadership Development. Issue 6 (November 2022) - Beal, Judy A.
Abstract: Background: Professional organizations have a long and rich history of promoting leadership development since the late 1800s. Professional nursing organizations and associations advocate for the profession of nursing and nurses, develop health care policies and standards that ensure the highest level of patient care quality, assure the highest level of education, provide professional development and continuing education, and offer research, networking, and career advancement opportunities for their members. Currently there are 10 nationally based pediatric nursing specialty organizations and associations, most of which also have regional or local chapters. Purpose: To use a scoping review to identify and summarize contributions of pediatric nursing organizations and associations in the United States to leadership development in pediatric nursing practice. Results: Although there are leadership programs sponsored by professional nursing organizations and mentions of leadership in their mission and "about us" statements, there is very little empirical evidence of the contributions that pediatric nursing specialty bodies make to the development of leaders. Conclusions: Membership in a professional nursing organization provides nurses with professional development; continuing education including journal subscription and conference attendance; networking; opportunities for specialty certification, career advancement, and leadership development; and research-based clinical standards and guidelines that promote best practice. The relationship between membership in pediatric professional organizations and leadership is clear in mission statements and strategic plans. Nurse leaders play a key role in advancing the organization's mission and goals. Nursing faculty, practice executives, and professional organizations and associations have an obligation to demonstrate value of membership in advancing the profession and developing future leaders. Future research is needed to describe the contributions of pediatric nursing professional organizations to leadership development of nurses. Abstract : In this scoping review, articles about pediatric specialty nursing associations and their role in leadership development were evaluated, along with the websites of the 10 current pediatric nursing specialty organizations. Although there are leadership programs sponsored by professional nursing organizations and mentions of leadership in their mission and "about us" statements, there is very little empirical evidence of the contributions that pediatric nursing specialty bodies make to the development of nurse leaders. Future research is needed to empirically support the value of professional organizations to their members.